SEKOLAH DASAR KONTEMPORER DENGAN FLEKSIBILITAS DAN KONEKTIVITAS RUANG SEBAGAI STRATEGI DESAIN - Martha Paramitha Maeliva; Maria Veronica Gandha (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
Information and Communication Technology has always been part of the lives of millennials, generation Z and Alpha, a significant difference in the learning process compared to previous generations. In the current educational environment, the meaning of "knowing" has shifted from being able to remember and repeat information to being able to find and use it. In an era with rapid technological development, student-centered learning environments are more constructivist and flexible and more suitable for building student’s knowledge. To prepare students for success in the development of the knowledge economy, new developments in the education system and learning environment are needed. The learning model in terms of curriculum, room quality, space configuration, and the program is adapted to the millennial teachers teaching behavior and generation Z and alpha students learning behavior so as to produce a collaborative learning environment between the millennial generation as teachers and generation Z and alpha as students. Contemporary schools with design strategies that provide flexibility, connectivity, freedom, space for social interaction and the education of their students. Curiculum and space programs that provide innovative elementary learning programs for indoor and outdoor play and learning taking into account children's physical, cognitive, emotional and social developmental aspects. Contemporary Elementary School is a mandatory formal education institution for children aged 7-12 years with a 6 years term that integrates contemporary education methods in the perspective of millennial, Z and Alpha.